Polymers for light-emitting devices and displays - Inamuddin, 1980-; Boddula, Rajender; Ahamed, Mohd Imran; Asiri, Abdullah M. (John Wiley & Sons, Inc., 2020)
"Polymers for Light-Emitting Devices and Displays provides an in-depth overview of fabrication methods and unique properties of polymeric semiconductors, and their potential applications for LEDs including organic electronics, displays, and optoelectronics. Some of the chapter subjects include : The newest polymeric materials and processes beyond the classical structure of PLED ; Conjugated polymers and their application in the light-emitting diodes (OLEDs & PLEDs) as optoelectronic devices ; The novel work carried out on electrospun nanofibers used for LEDs ; The roles of diversified architectures, layers, components, and their structural modifications in determining efficiencies and parameters of PLEDs as high-performance devices ; Polymer liquid crystal devices (PLCs), their synthesis, and applications in various liquid crystal devices (LCs) and displays ; Reviews the state-of-art of materials and technologies to manufacture hybrid white light-emitting diodes based on inorganic light sources and organic wavelength converters"--